2007
DOI: 10.1016/j.schres.2007.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of typical and atypical antipsychotics on brain myelination in schizophrenia

Abstract: Context-Imaging and post-mortem studies provide converging evidence that patients with schizophrenia have a dysregulated developmental trajectory of frontal lobe myelination even in adulthood. Atypical antipsychotics have been shown to have a wide spectrum of efficacy across multiple psychiatric diseases and to be particularly efficacious in treatment resistant cases of disorders such as schizophrenia.Objective-To test the a priori hypothesis that antipsychotic medications may differentially impact frontal lob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 78 publications
(126 reference statements)
6
73
0
2
Order By: Relevance
“…A recent DTI study showed that FA findings in FEP depended on the size of the studied sample [34]. More longitudinal study designs with large sample and uniform medication strategies, given that atypical and typical antipsychotics may differentially affect myelination in patients [50], are needed to draw robust conclusions on treatment responses. Future studies should also address comorbidities as they could be major sources of hetereogeneity in the biology of high-risk samples [51].…”
Section: Discussionmentioning
confidence: 99%
“…A recent DTI study showed that FA findings in FEP depended on the size of the studied sample [34]. More longitudinal study designs with large sample and uniform medication strategies, given that atypical and typical antipsychotics may differentially affect myelination in patients [50], are needed to draw robust conclusions on treatment responses. Future studies should also address comorbidities as they could be major sources of hetereogeneity in the biology of high-risk samples [51].…”
Section: Discussionmentioning
confidence: 99%
“…9,55 In addition, other reports have shown increased levels of serum lipids in patients treated with…”
Section: Effects Of Antipsychotic Drugs On Myelinationmentioning
confidence: 98%
“…There are, however, limited longitudinal in-vivo data regarding the potential impact of antipsychotics on the brain, and, in particular, the white matter. Some studies suggest that antipsychotics may have an important therapeutic role in promoting myelination through their effects on oligodendrocytes (Walterfang et al, 2011;Bartzokis et al, 2011), with some empirical work suggesting a protective or myelin-inducing effect of risperidone on the brain white matter (Bartzokis et al, 2007(Bartzokis et al, , 2011Bartzokis et al, 2009). Similarly, animal studies noted that antipsychotic treatment following administration of the copper chelator, cuprizone, promoted oligodendrocyte development and remyelination (Xiao et al, 2008;Zhang et al, 2012), which was evident from magnetic resonance (MR) imaging and confirmed by histological measures (Chandran et al, 2012).…”
Section: Introductionmentioning
confidence: 97%